Visible-light-driven palladium-catalyzed Dowd–Beckwith ring expansion/C–C bond formation cascade. Issue 5 (15th December 2020) - Chen, Li; Guo, Li-Na; Liu, Shuai; Liu, Le; Duan, Xin-Hua
Abstract : An intermolecular Dowd–Beckwith ring expansion/C–C bond formation is achieved through light-induced palladium catalysis. Not only styrenes but also the electron-rich alkenes such as silyl enol ethers and enamides were also compatible in this reaction. Abstract : A visible-light-induced palladium-catalyzed Dowd–Beckwith ring expansion/C–C bond formation cascade is described. A range of six to nine-membered β-alkenylated cyclic ketones possessing a quaternary carbon center were accessed under mild conditions. Besides styrenes, the electron-rich alkenes such as silyl enol ethers and enamides were also compatible, providing the desired β-alkylated cyclic ketones in moderate to good yields.